Mating Decreases Plasma Levels of Tgf?1 and Regulates Myosalpinx Expression of Tgf?1/Tgfbr3 in the Rat - Cardenas-Sankan, G; Orihuela-Diaz, P; Reuquen-Lopez, P; Diaz-Saldivar, P; Orostica, M (John Wiley and Sons Inc., 2014)
Mating shuts down a 2-methoxyestradiol (2ME)-dependent, non-genomic activity that is responsible for accelerating egg transport in the rat oviduct. The aims of this work were to investigate the role of TGF?1 in this 2ME-reduced activity and to determine the effect of mating on the expression and distribution of TGF?1 and its receptor TGFBR3 in the rat oviduct. We determined the level of TGF?1 in the plasma and oviductal fluid at 1, 3, or 6hr during Day 1 of the oestrous cycle in unmated or mated animals. We then examined if 2ME accelerates oviductal egg transport in unmated rats that were previously treated with a neutralizing TGF?1 antibody. The expression of Tgfb1 and Tgfbr3 mRNA and the level and distribution of TGFBR3 protein in the oviduct were also determined at these time points. Mating decreased TGF?1 in the plasma, but not in the oviductal fluid, whereas antibody neutralization of circulating TGF?1 did not prevent the effect of 2ME on egg transport. Mating decreased Tgfb1 and hastened the increase in TGFBR3 abundance in the myosalpinx. These results indicate that mating decreased circulating levels of TGF?1 without shutting down the non-genomic 2ME response that normally accelerates egg transport. Levels of Tgfb1 transcript and TGFBR3 protein, however, changed in the myosalpinx of mated rats, suggesting a role for mating-associated factors in the autocrine and paracrine effects of TGF? in the oviduct. © 2014 Wiley Periodicals, Inc.